2015
DOI: 10.1136/gutjnl-2015-309322
|View full text |Cite
|
Sign up to set email alerts
|

hTERT promotes the invasion of gastric cancer cells by enhancing FOXO3a ubiquitination and subsequent ITGB1 upregulation

Abstract: The hTERT/MDM2-FOXO3a-ITGB1 pathway markedly contributes to hTERT-promoted gastric cancer invasion, suggesting that this pathway might be a novel target for the prevention and treatment of gastric cancer metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(93 citation statements)
references
References 37 publications
6
87
0
Order By: Relevance
“…TERT induction/telomerase activation confers unlimited proliferation potential to cancer cells by stabilizing their telomere length, while recent observations reveal its multiple oncogenic activities independently of a telomerelengthening function, which include its effect on mitochondrial and ubiquitin-proteasomal function, DNA damage repair, gene transcription, microRNA expression, etc. [8][9][10][11][12][13][14][15][16]. Importantly, TERT was previously shown to promote the proliferation of normal mouse stem cells by recruiting chromatin-remodeling factor Brg1 to β-catenin target genes for their transcriptional activation [17]; and more recently, TERT was found to directly interact with β-catenin and robustly amplify its transcriptional outputs, thereby stimulating epithelial mesenchymal transformation (EMT) and stemness of cancer cells [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…TERT induction/telomerase activation confers unlimited proliferation potential to cancer cells by stabilizing their telomere length, while recent observations reveal its multiple oncogenic activities independently of a telomerelengthening function, which include its effect on mitochondrial and ubiquitin-proteasomal function, DNA damage repair, gene transcription, microRNA expression, etc. [8][9][10][11][12][13][14][15][16]. Importantly, TERT was previously shown to promote the proliferation of normal mouse stem cells by recruiting chromatin-remodeling factor Brg1 to β-catenin target genes for their transcriptional activation [17]; and more recently, TERT was found to directly interact with β-catenin and robustly amplify its transcriptional outputs, thereby stimulating epithelial mesenchymal transformation (EMT) and stemness of cancer cells [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…hTERT promotes the proliferation of different types of cancer [1922]. Previously, we observed that hTERT promotes the proliferation and invasion of gastric cancer via interactions with different genes [2325]. In addition, the suppression of hTERT could also inhibit the malignant activity of gastric cancer [26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…In gastric cancer, TERT was implicated in metastisation in several studies: (i) TERT-overexpressing cells had higher levels of Mac2-binding protein (Mac2BP) (Park et al 2007), a tumour antigen implicated in metastasis; (ii) TERT binds to c-MYC and recruits the complex to heparanase promoter to upregulate heparanase expression promoting invasion and metastasis of gastric cancer cells; furthermore, TERT-activated Wnt/B-Catenin signalling promotes c-MYC expression, which could in turn activate TERT transcription and expression in a positive feedback loop ; (iii) finally, it has been shown that TERT regulation of ITGB1 in the MDM2-FOXO3a-ITGB pathway is able to promote gastric cancer invasion (Hu et al 2015).…”
Section: Role Of Tert In Proliferation Invasion and Tumourigenesismentioning
confidence: 99%
“…Reduction of mtDNA damage Improvement of mitochondrial function Higher protection from apoptosis Prevention of nuclear DNA damage (Ahmed et al 2008) (Haendeler et al 2009) (Singhapol et al 2013) Cell death Nuclear TERT localization Diminished mtDNA damage Increase cell survival Protection against cellular senescence (Santos et al 2004) (Santos et al 2006) Nuclear TERT localization High DNA damage (Singhapol et al 2013) (Ding et al 2013) (Hu et al 2015) (Park et al 2007) ) ) ) ) (Liu et al 2013c) (Canela et al 2004) Invasion and metastisation TERT pathway selectively induces TERT mRNA expression in −146C > T mutant cells, in which the mutation creates a binding site specific for p52 that interacts with ETS factors ETS1/2 to mediate TERT reactivation (Li et al 2015b). This study also reports that there is an enhanced tumorigenic and proliferative effect due to NF-κB activation by the increase of telomerase activity dependent on the existence of −146C > T mutation (Li et al 2015b).…”
Section: Functional Effects Of Tert Promoter Mutations In Tumours Andmentioning
confidence: 99%